Analisis Efektivitas Pemberian Insentif Pajak Penghasilan Pasal 21 Ditanggung Pemerintah Pada Masa Pandemic Covid-19 (Studi Kasus KPP Madya Bekasi Tahun 2020 - 2021) - Nurhasanah, Fidiyah; Hidayati, Mainita; Gantino, Rilla (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2023)
The phenomenon in this study is the devastation of the covid-19 pandemic that has hit the whole world, including Indonesia, which has made a decline in the economic activity and productivity of business actors. Therefore the government was trying to provide stimulation fromthe tax sector in the form of providing incentives for Income Tax Article 21 borne by the government, the aim was to ease the tax burden so that business actors, especially employees, can maintain purchasing power during the difficult times of the covid-19 pandemic. The purpose of this study was to analyze the effectiveness of providing income tax article 21 incentives borne by the government. This study used a qualitative approach with a descriptive method. data collection techniques used the method of observation, interviews, and documentation. The results of this study showed the effectiveness in terms of taxpayers who take advantage of the Article 21 Income Tax incentives borne by the government in 2020 by 94% and in 2021 by 99%.